Loyalty-Based Portfolio Choice - Cohen, Lauren (Review of Financial Studies, 2009)
I evaluate the effect of loyalty on individuals' portfolio choice using a unique dataset of retirement contributions. I exploit the statutory difference that, in 401(k) plans, stand-alone employees can invest directly in their division, while conglomerate employees must invest in the entire firm, including all unrelated divisions. Consistent with loyalty, employees of stand-alone firms invest 10 percentage points (75%) more in company stock than conglomerate employees. Support is also found using variation in loyalty between different groups of employees, across and within firms. The cost to employees of loyalty is large, amounting to nearly a 20% loss in retirement income.